DDHD1, but Not DDHD2, Suppresses Neurite Outgrowth in SH-SY5Y and PC12 Cells by Regulating Protein Transport From Recycling Endosomes - Maemoto, Yuki; Maruyama, Tomohiro; Nemoto, Kazuaki; Baba, Takashi; Motohashi, Manae; Ito, Akihiro; Tagaya, Mitsuo; Tani, Katsuko (Frontiers in Cell and Developmental Biology, 2020)
DDHD1 and DDHD2 are both intracellular phospholipases A1 and hydrolyze phosphatidic acid in vitro. Given that phosphatidic acid participates in neurite outgrowth, we examined whether DDHD1 and DDHD2 regulate neurite outgrowth. Depletion of DDHD1 from SH-SY5Y and PC12 cells caused elongation of neurites, whereas DDHD2 depletion prevented neurite elongation. Rescue experiments demonstrated that the enzymatic activity of DDHD1 is necessary for the prevention of neurite elongation. Depletion of DDHD1 caused enlargement of early endosomes and stimulated tubulation of recycling endosomes positive for phosphatidic acid-binding proteins syndapin2 and MICAL-L1. Knockout of DDHD1 enhanced transferrin recycling from recycling endosomes to the cell surface. Our results suggest that DDHD1 negatively controls the formation of a local phosphatidic acid-rich domain in recycling endosomes that serves as a membrane source for neurite outgrowth.